The Role of First Language in Second Language Vocabulary Acquisition: An Investigation of a Bangladeshi Secondary School - Alimun, A. (University of Jaffna, 2025)
The main purpose of this study was to investigate the role of first language (L1) in second language (L2) vocabulary acquisition in a Bangladeshi secondary school context, with a focus on decolonizing English language learning practices. The research explores how students’ native language (Bangla) influences their capability to comprehend, translate, and retain English vocabulary. Data were obtained using a mixed-methods approach, including classroom observations, teacher interviews, student questionnaires, and focus group discussions across grades 6 to 8. The result of the study reveals that L1 facilitates the initial comprehension and retention of L2 vocabulary through code-switching and bilingual teaching approaches. This study also found that word-to-word translation discourages students from learning new vocabulary on their own. Thereby, they were not able to produce independent vocabulary learning strategies, carrying the colonial legacy of English education. Word (L2)-to-word (L1) translation is good for creating initial interest in English for the time being, but it restricts students’ eagerness to explore and learn new vocabulary. This study suggests further research is needed to initiate new pedagogy where translation should be used in a way that students should be interested to learn new vocabulary, breaking the cycle of colonial English language learning practice.
Keywords: L1; L2; Vocabulary acquisition; Bangladeshi secondary school; Decolonizing English language learning